(untitled) (The International Journal of Educational Sciences and Arts, 2024)
Violence has roots that go deep into antiquity, and its use began with the second generation of humanity, when Cain killed his brother Abel, thus committing the first crime in human history. This prompted thinkers, psychologists, and sociologists to say that violence is an instinct inherent in the human self and associated with human nature in its tendency to control and impose influence and domination. There have been many studies that have dealt with the subject of violence and that have come to addressing the subject of terrorism, and we find many of these studies that have defined it, and we also find that some of these studies and some governments, organizations and political figures intentionally and unintentionally confuse in many cases the phenomenon of terrorism with other human phenomena and problems. Other violent forms, such as national resistance, armed liberation movements, political crime, war, and the crime of genocide. In this analytical study, we will determine when terrorism transforms and acquires a political character? By analyzing political terrorism sociologically. We take into consideration two basic elements of this problem. The first is the subject of the phenomenon of political terrorism, or to whom the violent act of political terrorism occurs, and the second is the goal or objectives of practicing the act of political terrorism.